THE ROLE OF BEDSIDE BLADDER SONOGRAPHY FOR DETECTION OF BLADDER TRAUMA - Santoso, Jumadi; Adi, Kuncoro (Indonesian Journal of Urology, 2016)
Objective: To evaluate the role of bedside bladder sonography along with retrograde instilation of saline as a novel diagnostic procedure for suspected bladder trauma. Material & methods: Prospective evaluation of all patients with suspected bladder injuries admitted to the Emergency Department of Hasan Sadikin General Hospital, Bandung, Indonesia, from 2010–2013. Suspected urethral injury patients were excluded. Along with routine Focused Assessment Sonography for Trauma (FAST) procedure, bedside bladder sonography was performed concurrently with retrograde instillation of normal saline 350cc through a Foley catheter. The objective of real-time bladder sonogram was to examine the presence of peri-vesical free fluid turbulence and accumulation during saline instillation, which subsequently indicated a suspected bladder perforation. The accuracy of sonographic results were compared with computerized tomography (CT), cystogram or intraoperative findings. Time to diagnosis was recorded. Statistical analysis was performed to evaluate the sensitivity, specificity, positive predictive value (PPV), negative predictive value(NPV) and diagnostic accuracy. Results: 23 patients met the inclusion criteria. The mean age was 27.21 years old, 87% were males. Based on cystogram or intraoperative finding there are 21 patients have bladder rupture. Among these patients, 14 patients had positive result onbladder sonogram, and all confirmed positive on cystogram and operative finding. Nine patients had negative result on bladder sonogram. While 7 among them have positive result on cystogram or intraoperative finding. Analysis revealed 67% sensitivity, 100% specificity, 100% PPV, and 22.2% NPV. Overall diagnostic accuracy of bladder sonogram was 83.5%. Time to diagnosis were significantly shorter in bedside bladder sonogram compared to CT or cystogram (11.82 ± 2.99 min vs 181.30 ± 88.89 min; p < 0.05). Conclusion: Bedside bladder sonogram is a useful adjunct procedure for diagnosis of bladder trauma. It is time and cost effective, and can be performed in bed-side emergency setting with acceptable accuracy.